Analysis of long noncoding gene expression and its interactions with protein-coding genes in vascular endothelial cells in keloids - Yunxiang Luo; Zi Ye; Yi Li; Chau Wei Wong; Shuqia Xu; Yu Deng; Zhicheng Su; Xueqing Li; Yingxiong Huang; Bing Han (European Journal of Medical Research)
Abstract Objectives The purpose of this study was to determine the relationship between protein-coding RNA (messenger RNA, mRNA) and long noncoding RNA (lncRNA) expressed in vascular endothelial cells (VECs) in keloids by reanalyzing Gene Expression Omnibus (GEO) microarray chip data. Materials and methods The GSE121618 database and clinical information of these samples were downloaded and reanalyzed by the R language package. Expression differences in mRNA and lncRNA between keloids and normal skin were calculated. GO/KEGG enrichment analysis was conducted to determine the function of these genes, and an interaction network of lncRNAs–mRNAs was constructed. Magnetic Sorting of VECs and qRT-PCR were used to verify these bioinformatic results. Results The expression of three hundred and five mRNAs in the keloid group was significantly different from that in the normal group, and 98 lncRNAs were different, 21 of which were upregulated and 118 of which were downregulated. The hub relationship between the upregulated lncRNA‒mRNA interaction was lncRNA LINC01546–RASAL3/COL13A1, while the downregulated hub was lncRNA LOC101929787–PRKAA2/KRT71/SSTR1. qPCR verification result showed no obvious statistical differences. Conclusions Through the in-depth mining of keloid microarray data using bioinformatic methods, we speculated that VECs can affect the development and progression of keloids by epigenomic regulation via lncRNA‒mRNA interactions.